Factors Affecting the Performance of Sederhana Restaurant Employees in Bekasi - Yohanes Ferry Cahaya; Nadya Fitrimady; Ch. Endah Winarti; Annathasia Puji Erasashanti (Enrichment : Journal of Management, 2023)
With this intense competition in the culinary industry which forces various culinary companies to continue to improve the performance of their employees, including PT. Sederhana Abadanmitra. This study has purpose to identify and investigate further towards the factors which affecting the performance of Sederhana Restaurant employees that located in Bekasi area. These research objects were 3 restaurants of Sederhana which located in Bekasi such as Sederhana restaurant at Bekasi town Square, Sederhana Restaurant at Harapan Indah and Sederhana Restaurant at Caman with total respondents of 96 people who were employees of these three restaurants. SEM-PLS used as a tool in analyzed the data which capable to evaluated the outer and inner models. The results from this research shows 1) leadership style has insignificantly positive effect on employee performance 2) work environment has significantly positive effect on employee performance and 3) work motivation has significantly positive effect on employee performance.